Xiphinema llanosum and Trophurus vultus, two new plant nematode species from pasture soils in Colombia - Siddiqi, MR; Lenné, Jillian M. (1990)
Xiphinema llanosum n. sp. and Trophurus vultus n. sp. are described and illustrated from grass soils in Llanos Orientales, Colombia. Xiphinema llanosum is a bisexual species. The female body length is 2.3-2.7 mm, odontostyle 86-96 [mu]m, and odontophore 58-65 [mu]m long; vulva at 42-47%; anterior ovary is absent; the anterior uterus and oviduct are similar to the posterior branch but slightly reduced; and the tail is dorsally convex-conoid with a blunt hemispherical terminus. Male body length is 2.06-2.96 mm; spicules are 40-44 [mu]m long; and four (rarely three or five) anterior ventromedian supplementary papillae are present. Trophurus vultus females are 0.52-0.67 mm long; vulva at 56-60%; stylet is 10.5-13.5 [mu]m long; isthmus is as long as the basal esophageal bulb; the tail is subclavate, 1.6-2.2 times anal body width long; and the terminal cuticle thickness is about one-sixth of the tail length.